The significance of the European Fiscal Board in the surveillance of fiscal policy in the euro area – the two year experience with its operation and the prospects for the future - Giżyński, Juliusz (Znaczenie Europejskiej Rady Budżetowej w nadzorze polityki fiskalnej strefy euro – doświadczenia po dwóch latach funkcjonowania i perspektywy na przyszłość, 2019)
This article indicates the place of the European Fiscal Board in the fiscal supervision in the euro area, demonstrates the most important principles of the Board’s functioning, and presents the most important results of its two-year work. The Board acts as an independent advisory body to the European Commission. The outcomes of its work constitute an important voice in the debate on the new European fiscal framework. The article concludes with an evaluation of the Board’s functioning. On this basis, it has been concluded that the body is characterized by many limitations and therefore is a type of a low-significance fiscal council. A series of recommendations have been presented to strengthen its status. The research methods included in the work are a literature review and a comparative analysis of the documents issued by various institution of the European Union
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 22-39
Keywords: euro area; fiscal supervision; fiscal union; European Fiscal Board; strefa euro; nadzór fiskalny; unia fiskalna; Europejska Rada Budżetowa